Quality Management at Service Business: Theoretical and Methodological Aspects - Toymentseva, Irina A.; Sosunova, Lilyana A.; Kornev, Vyacheslav; Natalia, P. Karpova (International Review of Management and Marketing, 2016)
The article views the issues connected with the improving transport service that in the market conditions are closely related to the problems of quality. The aim of the research is the development of theoretical assumptions and methodology of enterprise strategic management of road transport services and the development of methods and models for decision-making. The study reveals the most important components (parameters) to measure the service quality, presents the main methods and models to determine the service quality; the characteristic of main incentives for the quality standard is given. The authors studied the factors of external and internal environment of Samara city, the results of which are presented in the form of SWOT-analysis; that is developed a modified technique to measure the quality of passenger transport services and determined its integral index on the basis of the data that are obtained by questioning passengers. The results of these studies led to the conclusion that there are significant reserves to improve the quality of passenger services. Keywords: dispersion; economic and mathematical model; integral index service quality; mathematical and statistical analysis; standard deviation; weighting factor. JEL Classification: C61